Analyzing the Economic Crisis in Venezuela: Causes, Effects, and Solutions - Raphaellee Peters Putra Usman; Moody Rizqy Syailendra Putra; Gunardi Lie (CV. Rayyan Dwi Bharata, 2023)
Venezuela in recent years has faced a severe decline in economic stability. Causes of the crisis can be attributed to economic mismanagement, over-reliance on oil, corruption and authoritarian rule. These factors have resulted in hyperinflation, poverty, collapsing public services and mass emigration. The effects of the crisis were profound, impacting the welfare of the Venezuelan people and creating a humanitarian emergency. In addition, the crisis has regional implications as neighboring countries grapple with accommodating Venezuela's migrants and refugees. To overcome the crisis, a comprehensive approach is needed, including fiscal discipline, economic diversification, strengthening democracy, and anti-corruption measures. Sound fiscal policies, structural reforms and international cooperation are critical to stabilizing the economy, attracting investment and driving sustainable growth. In addition, protecting vulnerable populations through targeted assistance programs and social safety nets is essential. However, effective solutions require a broader commitment to democratic governance, human rights and social cohesion. Rebuilding trust in institutions, promoting transparency and encouraging citizen participation are critical to long-term recovery.